Comparative studies of CdS thin films by chemical bath deposition techniques as a buffer layer for solar cell applications - Ashok, A.; Regmi, G.; Romero-Núñez, A.; Solis-López, M.; Velumani, S.; Castaneda, H. (Journal of materials science. Materials in electronics, 2020)
Cadmium sulfide (CdS) buffer layer that decouples the absorber layer and window layer in thin-film solar cells was synthesized by two different chemical bath deposition (CBD) techniques with varying deposition parameters. X-ray diffraction (XRD) revealed that the CdS thin film crystallizes in a stable hexagonal wurtzite structure having a preferential orientation along (002) reflection plane with a crystallite size varying from 20 to 40 nm. First longitudinal optical phonon mode was identified at Raman shift of 305 cm −1 . Uniform, granular, continuous, and smooth surface with an average grain sizes (< 100 nm) as well as small roughness (< 9 nm) was observed by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. The symmetric composition of cadmium and sulfur along with larger grains (20 nm) was observed at higher deposition temperatures and times. The optical band gap of CdS samples obtained from process one was in the range of 2.3–2.35 eV, while the band gap by the second CBD process lay in between 2.49 and 2.65 eV, showing the most stable compound of CdS. The presence of a green emission band in photoluminescence spectra (PL) demonstrated that the CdS material has better crystallinity with minimum defect density. Hall effect studies revealed the n-type conductivity of CdS thin films with a carrier concentration values in the order of 10 16 cm −3 . Furthermore, CdS thin films fabricated by CBD process exposed better quality that might be more suitable material as a buffer layer for thin-film solar cells.